Application of the Al-Barā'ah Al-Dhimmah Method According to Fiqh Law and Its Implementation in Current Legislation in Malaysia - Nik Faisal Nik Ismail (Rabbanica: Journal of Revealed Knowledge)
This article discusses the application of the principle of original freedom (al-asl barÉah al-zimmah) according to Islamic jurisprudence and its implementation in current legislation in Malaysia. The objective of this study is to demonstrate the important role of the stated principle in addressing various issues related to family matters, transactions, and crimes. This study is qualitative in nature and based on a framework of content analysis. Data collection involves referring to exegesis books, Sunnah, classical fiqh texts, principles of jurisprudence, al-Qawaid al-Fiqhiyyah, views of contemporary Islamic scholars, current laws, and content research. The collected data is analyzed and interpreted using deductive, descriptive, and comparative methods to obtain appropriate findings in line with the established research objectives. The results of the study indicate that this principle emphasizes the principle of al-baréah (freedom) possessed by every human being from being burdened with obligations, responsibilities, accusations, or punishments. Findings also show that this principle is based on the Quran and Sunnah and can be applied in various branches of Islamic law, playing a significant role in realizing justice for parties involved in disputes, especially in the aspects of family matters, transactions, and crimes. The implementation of the theories and principles found in this principle will ensure the preservation of the rights and dignity of every individual from both Islamic law and current legislative perspectives.